Synergy between Acute Intermittent Hypoxia and Task-Specific Training. Issue 3 (July 2020) - Welch, Joseph F.; Sutor, Tommy W.; Vose, Alicia K.; Perim, Raphael R.; Fox, Emily J.; Mitchell, Gordon S.
Abstract : Acute intermittent hypoxia (AIH) and task-specific training (TST) synergistically improve motor function after spinal cord injury; however, mechanisms underlying this synergistic relation are unknown. We propose a hypothetical working model of neural network and cellular elements to explain AIH-TST synergy. Our goal is to forecast experiments necessary to advance our understanding and optimize the neurotherapeutic potential of AIH-TST. Abstract : Summary for table of contents: This article puts forward a hypothetical working model of synergy in motor plasticity induced by combined acute intermittent hypoxia and task-specific training.